2008
DOI: 10.1002/pat.1026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of take‐up speed on the structure and properties of melt‐spun poly(L‐lactic acid) fibers

Abstract: Poly(L-lactic acid) (PLLA) filament fibers were prepared by one-step melt spinning process and the effects of variations in take-up speed on their thermal properties, mechanical properties, and crystalline structures were investigated. Differential scanning calorimetry (DSC) results revealed that the PLLA fibers showed multiple melting peaks and that the melting peak appearing at a lower temperature moved lower while that at a higher temperature moved higher with increasing take-up speed. The glass transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…The measured linear densities, birefringence, refractive indices and overall orientation function of the T and J samples are presented in Table 1. The measured birefringence showed reasonable agreement with the reported literature data in the range of 0.015-0.025, increasing by the takeup speed [25]. The filaments appeared yellowish-red between cross-polarized optical microscope, which was consistent with the previous reports regarding samples with positive birefringence [9,13,25].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The measured linear densities, birefringence, refractive indices and overall orientation function of the T and J samples are presented in Table 1. The measured birefringence showed reasonable agreement with the reported literature data in the range of 0.015-0.025, increasing by the takeup speed [25]. The filaments appeared yellowish-red between cross-polarized optical microscope, which was consistent with the previous reports regarding samples with positive birefringence [9,13,25].…”
Section: Resultssupporting
confidence: 92%
“…Detailed thermomechanical analysis of the PLA fibers revealed storage modulus, E′, loss modulus, E″ and tan δ curves sensitivity to fiber structure. The experimental results confirmed that the thermomechanical properties of PLA fiber were affected by changes in fiber collection speed, drawing force and physical aging due to the changes in the fiber structural features included crystallinity, molecular orientation [8,25], microfibril size [14] and crystal structure [27]. The enhanced fiber crystallinity and chain orientation restricted the amorphous phase molecular mobility and improved its glass transition and modulus profoundly [8,14].…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations